Decision Support System For Employee Performance Assessment Using Smart Method at The Public Housing Service And Settlement Area of Musi Rawas Regency - Annes, Annes yusnara; Sekar, Sekar Ayu Fitria; Roy, Roy Meican Tri; Aliyah, Aliyah Azizah; Rizki, M. Rizki Ibnu Sandy; Bagas Miswanto; Novi Lestari; Satrianansyah (Adpebi Science Series, 2022)
Abstract This study found that a decision support system to evaluate the performance of personnel in public housing services and district housing zones has not been established. Rawas composed the music. Observation and direct recording at the research site (observation), interviews with resource persons (interviews), and documentation by reading existing books and literature (documentation) are some of the ways this research collects data (documentation research). Based on research conducted at the Department of Public Housing and residential areas in Musi Rawas Regency, the author makes a decision support system application that helps the community in evaluating their work. There may be a decision support system for assessing employee performance based on a discussion of the analysis that has been carried out. This system can be used to evaluate employee performance using the SMART method as a method of decision making. With this system made, it can help the assessment team determine which employees deserve to be the best employees according to the criteria applied.